Metode Pastoral Konseling Remaja Kristen yang Mengalami Kesepian Kronis - Bernat Keristovel Sologi; Yanto Paulus Hermanto (Indo Publishing, 2026)
The results of a survey on adolescent mental health in 2015 from WHO showed a high figure, namely more than 1.63 million teenagers in Indonesia experienced loneliness. Teenagers always describe their loneliness as feeling empty, bored and isolated. Chronic loneliness can last a long time and people who experience it can socialize with other people but do not get intimacy in these interactions. This research uses qualitative literature study methods to answer this research problem. Pastoral counseling methods to help teenagers who experience chronic loneliness include: 1) forming good relationships 2) listening with empathy 3) helping teenagers identify feelings 4) developing social skills 5) encouraging spiritual growth